Frank Wood's business accounting 1 Frank Wood 1926-2000 - Sangster, Alan; Gordon, Lewis (Financial accounter); Wood, Frank 1926-2000 (Pearson Education, 2018)
Frank Wood's Business Accounting Volume 1, the world's best-selling textbook on book-keeping and accounting, continues to provide an indispensable introduction for students and professionals across the globe.